Pakistan's Fourth military coup / edited by Aftab Alam - "Alam,Aftab.( ed.)" (New Delhi, 2001)
This book is a comprehensive study of Pakistan's fourth military coup.The coup d'etat of October 12, 1998 led by General Pervaiz Musharraf which displaced Sharif's civilian government was the reassertion of the military's dominant role in the polity after an interval of 11 years. However, there is a difference between this coup and the past ones. Unlike earlier coups which has been proactive, where in the military sought political power, the present one only amounts to a reactive coup. In this case, the military did not initiate matters but was clearly compelled to react to the moves of the elected leadership which where aimed at destroying its institutional existence.
Keywords: National security-Pakistan